Proceedings of the 29th Conference on Winter Simulation - WSC '97 1997
DOI: 10.1145/268437.268752
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Queston Physician Network

Abstract: This paper examines the construction and implementation of a simulation model that supports the design and development of the Queston Physician Network. Queston seeks to partner with health care professionals to provide high quality, cost-effective medical care. Towards this end, a simulation model encompassing both the operations of a Queston clinic and a Queston Information Center has been developed. This model is built in an object-oriented, visual manner utilizing the Visual Simulation Environment (VSE). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…They tested three different alternatives for scheduling patients for ENT physicians and ended up selecting a policy that reduced the average patient wait time by 45% (Kachhal et al 1981). Swisher et al (1997) showed that under certain conditions staffing reductions could be made without sacrificing patient throughput or increasing staff overtime. They experimented with several models mixing different types of patients (Swisher et al 1997).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They tested three different alternatives for scheduling patients for ENT physicians and ended up selecting a policy that reduced the average patient wait time by 45% (Kachhal et al 1981). Swisher et al (1997) showed that under certain conditions staffing reductions could be made without sacrificing patient throughput or increasing staff overtime. They experimented with several models mixing different types of patients (Swisher et al 1997).…”
Section: Related Workmentioning
confidence: 99%
“…Swisher et al (1997) showed that under certain conditions staffing reductions could be made without sacrificing patient throughput or increasing staff overtime. They experimented with several models mixing different types of patients (Swisher et al 1997). They also showed that scheduling more of a certain type of patient (patients that require extensive physician interaction; longer service time) in the morning reduces employee overtime significantly.…”
Section: Related Workmentioning
confidence: 99%
“…Little evidence of implementation was presented. 5.6 Modelling flows between the above departments, and whole system models Jun et al [3] identify multi-facility simulation models conducted by Hancock and Walters [100], Swisher et al [101] and Lowery and Martin [74].…”
Section: Summary-diagnostics Modelsmentioning
confidence: 99%
“…Such issues can also affect how hospital resources are optimized to facilitate patient flow and reduce patient waiting time. Several studies have been conducted to show that there is a link between patient scheduling and admission policies and patient waiting time (Fitzpatrick et al , 1993; Klassen and Rohleder, 1996; Swisher et al , 1997; Kim et al , 2014). Another factor in reducing patient’s waiting time is the use of a fast track lane to reduce waiting times for low-priority non-urgent patients.…”
Section: Background and Introductionmentioning
confidence: 99%